2019
DOI: 10.1026/2191-9186/a000442
|View full text |Cite
|
Sign up to set email alerts
|

Sind Fortbildungsmaßnahmen zu linguistisch fundierter Sprachförderung wirksam?

Abstract: Zusammenfassung. Ziel des Beitrags ist es, die Effektivität einer Fortbildungsmaßnahme zu linguistisch fundierter Sprachförderung zu untersuchen. In einem Prätest-Posttest-Kontrollgruppen-Design wurden die Sprachförderkompetenz von Fachkräften ( n = 33) und die produktiven Sprachfähigkeiten der von ihnen geförderten mehrsprachigen Kinder ( n = 78) in den Bereichen Satzstruktur und Kasus erhoben. Die Sprachförderkompetenz der pädagogischen Fachkräfte aus der Experimentalgruppe ( n = 18) war nach Abschluss der F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
2
8
0
1
Order By: Relevance
“…Therefore, linguistically oriented models such as that developed by Hopp et al (2010) provide a basis for planning specific training programs for language support. Training programs administered in studies investigating knowledge and skills focused on different content, i.e., on the usage of LSS (Beckerle et al, 2019) or on linguistic and practical knowledge (Roth et al, 2015;Lemmer et al, 2019). Overall, these studies found positive effects of intervention programs on the caregivers' knowledge and theoretical competencies (Roth et al, 2015;Beckerle et al, 2019).…”
Section: Professionalization Of Caregivers In Early Childhood Educationmentioning
confidence: 92%
See 3 more Smart Citations
“…Therefore, linguistically oriented models such as that developed by Hopp et al (2010) provide a basis for planning specific training programs for language support. Training programs administered in studies investigating knowledge and skills focused on different content, i.e., on the usage of LSS (Beckerle et al, 2019) or on linguistic and practical knowledge (Roth et al, 2015;Lemmer et al, 2019). Overall, these studies found positive effects of intervention programs on the caregivers' knowledge and theoretical competencies (Roth et al, 2015;Beckerle et al, 2019).…”
Section: Professionalization Of Caregivers In Early Childhood Educationmentioning
confidence: 92%
“…Other studies from German-speaking countries set their focus on the standardized assessment of caregivers' knowledge and skills rather than on observing the performance of language support (e.g., Roth et al, 2015;Beckerle et al, 2019;Lemmer et al, 2019), as different types of knowledge are considered prerequisites for, for example, the quality of teaching and students' competencies (e.g., Yang et al, 2020). Models exist describing the competencies required for successful language support.…”
Section: Professionalization Of Caregivers In Early Childhood Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…B. . Wie gut sich fachintegriertes sprachliches Scaffolding eignet, um die sprachlichen Kompetenzen von einsprachigen und mehrsprachigen Lernenden in einsprachigen Lernumgebungen zu fördern, ist somit zumindest für den Schulkontext noch weitgehend ungeklärt (für den Vorschulbereich siehe Lemmer et al, 2019). Für die stärker strukturierten Ansätze zur Förderung des bildungssprachlichen Wortschatzes zeigten sich indes positivewenn auch zum Teil nur kleine -Effekte auf den in der Intervention vermittelten Wortschatz (z.…”
Section: Sprachliches Scaffolding Und Förderung Des Bildungssprachlic...unclassified